Game Bertema Cerita Rakyat “Si Kerudung Merah Dan Sang Serigala” dengan Metode Pengembangan Game Development Life Cycle - Nadea Cipta Laksmita; M Fairul Filza; Bayu Setiaji; Akbar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The design and manufacture of a survival puzzle themed game is made using the 2d-based unity engine. This game is intended for the android platform. The development stages include analysis, design, development, implementation, and testing. If the test meets the criteria, then a feasibility test will be carried out in the field. It is hoped that with game development, indie developers can contribute to the game industry and add insight to other developers. It is hoped that after making this game, it can add to the list of games made by Indonesian developers and become a motivation for other developers to continue to develop. In this thesis itself will discuss the methods used by developers to develop games, the description of the scripts that will be used, how to implement them on Android, as well as the initial stages in designing a Unity-based Android game. It is also hoped that this thesis can be a reference for students who are interested. with the world of games. From the results of the beta stage trial percentage, it can be seen that the result of the total percentage calculation is 88.46%. Judging from the interval and the percentage results show that the player's testing of The Red Riding Hood and The Wolf game belongs to the "Very Good" category